An experimental analysis of single pass cutting of aluminium 5083 alloy in different corner angles through WEDM. (1st January 2013) - Selvakumar, G.; Sarkar, S.; Mitra, S.
The experimental research presented in this paper deals with the concurrent optimisation of the responses namely cutting speed, surface roughness and corner inaccuracy during wire electrical discharge machining (WEDM) of aluminium 5083 alloy. The aluminium 5083 is magnesium-based aluminium alloy predominantly used in marine, cryogenic and aerospace applications. The conventional means of processing of 5083 AA is difficult as it exhibits poor machinability and average workability in the context of producing intricate shapes with very high precision and accuracy. WEDM is one of the lucrative machining techniques to process this alloy. Experiments have been performed based on L-18 orthogonal array with pulse on time, pulse off time, peak current, wire tension, servo feed setting and corner angle as control factors. ANOVA was performed to find the significance of the factors considered. Taguchi's additive model was used for prediction. Later, the responses were concurrently optimised based on Pareto optimality approach and a technology table has been tailored for handy use.